cents_analysis_v1.0 - Ribeiro, Felipe de Almeida (Revista Vórtex, 2014)
Computer music patch/abstraction developed with Max 7 (Cycling74) for frequency analysis and music notation. It features a microtonal interval calculator alongside an interface for musical notation. This patch was made for those who deal with the notation of microtonal music.